Incorporation of indigenous microorganisms increases leaching rates of rare earth elements from western australian monazite - Corbett, M.; Eksteen, Jacques; Niu, X.; Watkin, E. (2017)
© 2017 Trans Tech Publications, Switzerland. A large number of microbial species commonly called phosphate solubilizing microorganisms (PSMs) are efficient at converting insoluble phosphate to soluble forms to prevent phosphorus limitation. This study examined the impact that PSMs had on a sterile and non-sterile monazite source and determined that they could be applied for bioleaching purposes to recover rare earth elements (REEs). On sterile monazite, Penicillium sp. released a total REE concentration of 12.32 mg L -1 after incubation for 8 days, however, this doubled when inoculated on to non-sterile ore (23.7 mg L -1 ). Similar results were recorded with Enterobacter aerogenes, Pantoea agglomerans and Pseudomonas putida. Abiotic controls leached a total REE level of 0.65 mg L -1 . Examination of the leachate by HPLC identified several low molecular weight organic acids that corresponded with decreases in the media pH. The presence of a native consortia from the monazite ore combined with a known PSMs was more effective at leaching REEs from the monazite matrix than a single isolates or by the native population alone.